The Project Workout: The Ultimate Guide to Directing and Managing Business-Led Projects - Robert Buttrick (New York Routledge, 2019)
Projects are an important strategic management tool and a way of life in every business. But how do you get started and ensure you realize the benefits you need? Now in its 5th edition, the Project Workout is the definitive book on business-led project management. It is a valuable companion for every executive and project manager as well as a comprehensive resource for students of project management.
Keywords: Project management; Management; (BIN3043-N) Project-Based Management